Potential impact of sodium glucose co-transporter (SGLT2) inhibitors on cholesterol fractions in stage 3 chronic kidney disease - Rabab Mahmoud Ahmed; Nehal Kamal Rakha; Ahmed Yousry; Amin Roshdy Soliman (SpringerOpen, 2024)
Abstract Introduction Data on sodium glucose co-transporter 2 inhibitors impact on lipids in patients with diabetes are available and only a handful of studies have explored this effect in individuals with both diabetes and renal impairment; lipid parameters were not the primary focus of those earlier studies. However, there is a significant research gap specifically addressing the influence of SGLT2 inhibitors on cholesterol fractions in patients exclusively with chronic kidney disease. This aim constitutes the central objective in this particular study. Methods In this 3-month randomized controlled study, 30 patients with stage 3 chronic kidney disease and dyslipidemia were randomly assigned to receive either dapagliflozin 10 mg or placebo. Lipid profiles, renal function, and urinary albumin levels were assessed at baseline and after 3 months. Results Compared to baseline, patients receiving dapagliflozin for 3 months showed significant improvements in serum creatinine (p < .001) and eGFR (p = .001). Total cholesterol and LDL-C levels decreased significantly (p = .010 and .006, respectively). While albumin-creatinine ratio also decreased, this change was not statistically significant. Additionally, HDL-C and TG not significantly increased. The control group without intervention experienced deterioration in serum creatinine and eGFR (p = .008, and .011, respectively), but no statistically significant lipid changes were observed. Furthermore, post-intervention total cholesterol moderately correlated with BMI (p = .032, R = .554), yet no predictors significantly influenced lipid levels in the multiple linear regression analysis. Conclusions Dapagliflozin has a favorable effect on cholesterol fractions in stage 3 CKD patients without diabetes mellitus and this effect was different from that observed in patients with diabetes alone.